IMPLEMENTASI SISTER PROVINCE PROVINSI JAWA TENGAH DENGAN NEGARA BAGIAN QUEENSLAND AUSTRALIA DI BIDANG PERTANIAN - Windiani, Reni (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2014)
Globalization on national context has insisted the central government to work together and share duties and rights with the local government in order to achieve the national interest. In Indonesia, UU 32/2004 about local government provide the chance for them to become more active in foreign policy, such as doing the cooperation in sister province/sister city program.The Central Java Province had done many sister province/sister city program with some partners aboard, such as Fujian province (China), Chungchoeng buk-do province (South Korea) and the Queensland province (Australia). The cooperation cover many sectors such as agriculture, city and village development, transportation and tourism, industry, trade and infestation, education, science and technology, and other sectors that will be confer in advance.From all of the cooperation that have been done between Central Java Province and Queensland, the author, is interested to have research on farming, because central government has had many cows imported from Australia. This research is become important because central java province is one of the major of national fresh meat distributors.This research is using a qualitative method, with descriptive type of research. This research has three research questions: How effective is the Sister Province program in Central Java with the Queensland in farm sector? What is the obstacle that holds the Sister Province program in Central Java with the Queensland in farm sector? How is the prospect of Sister Province program in Central Java with the Queensland in farm sector?This result of this research is to prove that the implementation of Sister Province program in Central Java with the Queensland in farm sectors is not effective. Some of the implementation variables of this program have not been fulfilled.Communication, financial resources and bureaucracy structure are some of the variables that have weakness on this program. Act of Internal Affairs (Permendagri) Number. 03/2008, about equality in administration status, equivalent characteristics and problems has not been notice. The absence of a good authority in animal husbandry department and in the province of Central Java for the procurement of imported cows had influence this issues. The authority lies in the central government through the Ministry of Agricultural.